Pengaruh Nilai Tukar Rupiah serta Tingkat Suku Bunga Terhadap Penerimaan Pajak pada Direktorat Jenderal Pajak - Ai Nety Sumidartini (Institut Ilmu Sosial dan Manajemen STIAMI, 2017)
Acceptance receiving of Tax is one of source of acceptance receiving of biggest state compared to acceptance receiving from sector migas and acceptance receiving of other state. Tax gives contribution of acceptance receiving 70,46 % to APBN the year 2007.Acceptance receiving of Tax cannot be independent separated from macro factor of other chartered investment counsel of sebagimana has been disumsikan at the time of compilation APBN, like chartered investment counsel growth, rupiah conversion value, level of interest rate, level of the price of commodity exchange incorporated at international market, and commodity exchange incorporated production rate in country. Macro factor of the chartered investment counsel haves the character of dynamic and changes as according to condition of run economics at that moment while acceptance receiving plan of Pajak has been specified beginning of year as according to pegging of Anggaran and Pendapatan Belanja Negara.To check whether there or is not there influence from alteration of macro factor of the chartered investment counsel to tax acceptance receiving, hence at this research will be studied about rupiah conversion value influence, and level of interest rate to acceptance receiving of tax at Tax Directorate General.To answer the problems, data collected from various sources and analysed with associative method ( relationship) is having the character of interaktif resiprokal or is each other influence. Research variable data collected to be checked with linear regression passed testing of linierity and testing of classic assumption.Result of research shows existence of influence signifikan to level of rupiah conversion value, and level of interest rate to acceptance receiving of good tax x'selfly ( parsial ) and also joinly ( simultan ).